Stamping of forgings with side outlets of tee-type in a split tool - V. V. Gryaznov; V. A. Konovalov; D. A. Kormakov; I. V. Markechko; E. N. Merkushev (Омский научный вестник, 2025)
The article considers the options for analyzing design and technological solutions for hot volume stamping of tees in split dies on a double-action crank hot stamping press. The analysis technique is based on assessing the parameters of shaping with acceptable changes in the shape and size of the shaping tool engraving and the dimensions of the blanks. Modern research methods are used, accompanied by a technology design cycle from setting the initial conditions to creating a 3D model of stamped forgings and manufacturing the tool. The developed algorithm for designing the technology allows for simplifying and accelerating the process of preparing for the production of forgings. In conclusion, the factors that determine the possibilities of improving the quality of stamped products are presented, and directions for possible improvement of the technology for stamping forgings of parts with tee-type processes are proposed.